Kaznakhtite, Ni6Co3+2(CO3)(OH)16⋅4H2O, a new natural layered double hydroxide, the member of the hydrotalcite supergroup. (21st October 2022) - Kasatkin, Anatoly V.; Britvin, Sergey N.; Krzhizhanovskaya, Maria G.; Chukanov, Nikita V.; Škoda, Radek; Göttlicher, Jörg; Belakovskiy, Dmitry I.; Pekov, Igor V.; Levitskiy, Victor V.
Abstract: Kaznakhtite, ideally Ni6 Co 3+ 2 (CO3 )(OH)16 ⋅4H2 O, is a new member of the hydrotalcite group within the hydrotalcite supergroup. The mineral was discovered at the Kaznakhtinskiy ultrabasic massif, Altai Republic, SW Siberia, Russia. It occurs as powdery aggregates forming flattened lenses up to 1.5 × 0.5 cm and veinlets up to 1 cm long and up to 1 mm thick in aggregates of chrysotile, lizardite, stichtite and dolomite. Other associated minerals include brucite, chromite, heazlewoodite, manganochromite, magnetite and magnesioferrite. Kaznakhtite aggregates are composed of tiny platy grains up to 0.01 mm across. Kaznakhtite is light green and translucent in aggregates. It has an earthy lustre and white streak. Cleavage is micaceous on {001}. D calc = 2.864 g cm –3 . The mineral is optically uniaxial (–) with ɛ = 1.657(3) and ω = 1.676(3), and weakly pleochroic in greenish hues, ω > ɛ. Chemical composition (wt.%, electron microprobe, Co valence state determined by XANES spectroscopy, CO2 and H2 O calculated by stoichiometry) is: MgO 2.15, NiO 47.40, ZnO 0.22, Al2 O3 0.16, Cr2 O3 0.98, Co2 O3 17.42, Cl 0.63, CO2 5.05, H2 O 24.60, –O=Cl –0.14, total 98.47. The empirical formula calculated based on the sum of all metal cations = 8 apfu is (Ni5.54 Mg0.47 Zn0.02 )Σ6.03 (Co 3+ 1.83 Cr0.11 Al0.03 )Σ1.97 C1.00 O2.99 (OH)15.84 Cl0.16 ⋅4H2 O. Infrared spectroscopy confirmed the presence of CO3 2– anions, OH – groups and H2 O molecules. The crystal structure was refined by the Rietveld method with R B = 0.19%. Kaznakhtite is trigonal, space group R͞ 3 m, a = 3.0515 (3), c = 23.180 (3) Å, V = 186.93 (4) Å 3 and Z = 3/8. The strongest lines of the powder X-ray diffraction pattern [ d, Å ( I, %) ( hkl )] are: 7.72 (100) (003); 3.863 (24) (006); 2.630 (4) (101); 2.576 (10) (012); 2.294 (6) (015); 1.950 (4) (018); 1.526 (4) (110); and 1.497 (4) (113). Kaznakhtite is a Co 3+ analogue of reevesite, Ni6 Fe 3+ 2 (CO3 )(OH)16 ⋅4H2 O. The mineral is named after its type locality.